Intestinal complications of Behçet’s disease - Kovacs, D Botond (BMJ Publishing Group, 2013)
We report a case of a young female patient with long-standing oral and genital Behçet’s disease (BD), who presented with progressive severe colonic inflammation and perforation, requiring multiple laparotomies. The case had ultimately a favourable outcome despite posing a number of diagnostic and therapeutic challenges. Intestinal complications, although rare, should be considered as important differential diagnoses in patients with BD presenting with abdominal pain, and is a difficult-to-prove differential diagnosis to Crohn's disease.